2014
DOI: 10.1007/s10719-014-9541-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between ceramide and ionizing radiation

Abstract: The aim of radiotherapy is to eradicate cancer cells with ionizing radiation; tumor cell death following irradiation can be induced by several signaling pathways, most of which are triggered as a consequence of DNA damage, the primary and major relevant cell response to radiation. Several lines of evidence demonstrated that ceramide, a crucial sensor and/or effector of different signalling pathways promoting cell cycle arrest, death and differentiation, is directly involved in the molecular mechanisms underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 74 publications
1
36
0
1
Order By: Relevance
“…Ceramide is localized within lipid rafts in the plasma membrane, which are specialized membrane microdomains that regulate various signaling pathways (105). Ceramide is also a central molecule of sphingolipid metabolism and involved in the regulation of autophagy at various levels (106,107). Ceramide downregulates the expression of Figure 2.…”
Section: Ceramide and Autophagymentioning
confidence: 99%
See 2 more Smart Citations
“…Ceramide is localized within lipid rafts in the plasma membrane, which are specialized membrane microdomains that regulate various signaling pathways (105). Ceramide is also a central molecule of sphingolipid metabolism and involved in the regulation of autophagy at various levels (106,107). Ceramide downregulates the expression of Figure 2.…”
Section: Ceramide and Autophagymentioning
confidence: 99%
“…Ceramide accumulation also can induce ER stress, mTOR inhibition via TRB3 (tribbles homologue 3), which triggered lethal autophagy (111)(112)(113). Moreover, ceramide can be generated by neutral sphingomyelinase in mitochondria, which is a late event upon the cell irradiation following the early phase of ceramide accumulation at the cell plasma membrane (106). Ceramide accumulation in the mitochondria can lead to ceramide stress-induced mitochondrial fragmentation, and decrease in ATP production (114).…”
Section: Ceramide and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to chemotherapeutics, radiotherapy is frequently limited to tumor locations and not systemic. By using high-energy liberation of electrons, it is possible to induce cell death specifically in malignant cells (Aureli et al, 2014). This process occurs by induction of DNA damage, as radiation causes double-strand breaks in DNAs that are lethal to cells (Beckham, Cheng, et al, 2013; Carroll, Donaldson, & Obeid, 2015).…”
Section: Effects Of Chemo- and Radiation Therapieson Sphingolipidsmentioning
confidence: 99%
“…Numerous studies have demonstrated that ionizing radiation and DNA damaging chemotherapeutic drugs induce growth arrest and apoptosis of various cancer cells in part through generation of ceramide [ 119 ] or SPH [ 72 ]. Consequently, it is possible that these bioactive sphingolipids also mediate the therapeutic action of imiquimod or fl uorouracil in NMSC.…”
Section: Potential Roles Of Sphingolipids In Nmsc Therapymentioning
confidence: 99%